ANALYSIS OF THE ROLE OF KODIM 1309/MANADO IN STRENGTHING GOVERNMENT TO DEAL WITH FLOODING IN MANADO CITY: Analisis Peran Kodim 1309/Manado Dalam Penguatan Kapasitas Pemerintah Daerah Untuk Penanggulangan Banjir di Kota Manado - Robby Moechammad Taufik; Djoko Andreas Navalino; Daniel E S (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the role of Kodim 1309/Manado in strengthening the capacity of the Manado City Government for flood management. Manado City faces high flood risks due to its hilly topography, the presence of the Tondano River, and intense rainfall. Kodim 1309/Manado, as part of the Indonesian National Army, holds a strategic role in supporting mitigation, emergency response, public education, and post-disaster recovery as part of Military Operations Other Than War (MOOTW). However, its effectiveness is often constrained by limited trained human resources, inadequate mastery of modern technologies such as drones and insufficient operational budgets. This research employs a qualitative descriptive method with a case study approach to explore the role of Kodim in greater depth. The findings reveal that Kodim excels in personnel and logistics mobilization but requires improvements in technology adoption and cross-sector collaboration. Through SWOT analysis, this study formulates strategies to optimize Kodim’s role, including leveraging modern technology, developing human resource capacity, strengthening synergy with government agencies and communities, and adopting green infrastructure for sustainable flood mitigation. The results of this study are expected to provide a foundation for enhancing Kodim’s role in addressing future flood challenges. By implementing technology-based strategies, cross-sector collaboration, and community empowerment, Kodim 1309/Manado can serve as a model for more effective and efficient disaster management.